Microbial Corrosion of API 5L X-70 Carbon Steel by ATCC 7757 and Consortium of Sulfate-Reducing Bacteria - Arman, Abdullah; Nordin, Yahaya; Norhalizan, Md Noor; Rosilawati, Mohd Rasol (Hindawi Publishing Corporation, 2014)
Various cases of accidents involving microbiology influenced corrosion (MIC) were reported by the oil and gas industry. Sulfate reducing bacteria (SRB) have always been linked to MIC mechanisms as one of the major causes of localized corrosion problems. In this study, SRB colonies were isolated from the soil in suspected areas near the natural gas transmission pipeline in Malaysia. The effects of ATCC 7757 and consortium of isolated SRB upon corrosion on API 5L X-70 carbon steel coupon were investigated using a weight loss method, an open circuit potential method (OCP), and a potentiodynamic polarization curves method in anaerobic conditions. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were then used to determine the corrosion morphology in verifying the SRB activity and corrosion products formation. Results from the study show that the corrosion rate (CR) of weight loss method for the isolated SRB is recorded as 0.2017 mm/yr compared to 0.2530 mm/yr for ATCC 7757. The Tafel plot recorded the corrosion rate of 0.3290 mm/yr for Sg. Ular SRB and 0.2500 mm/yr for Desulfovibrio vulgaris. The results showed that the consortia of isolated SRB were of comparable effects and features with the single ATCC 7757 strain.